Counseling on balanced nutrition 'isi piringku' to prevent stunting in toddlers aged 1-5 years - Imardiani Imardiani; Dodik Firnando; Triya Cindy Franciska; Riska Wulandari; Tiara Medira; Intan Pramono; Wanda Hamidah; Suci Romadhona; Indah Tri Lestari; Intan Nurmala (Universitas Muhammadiyah Magelang, 2024)
Toddlers are a vulnerable group affected by child nutrition issues, one of which is stunting. Stunting is a condition where a child experiences growth impairment, resulting in their height not matching their age due to chronic nutritional problems, specifically prolonged nutrient deficiency. Stunting is caused by two factors: the history of exclusive breastfeeding and maternal knowledge about nutrition. This community service activity aims to increase public knowledge about balanced nutrition guidelines through the